Book Tax Differences, Operating Cash Flow, Leverage and Earning Persistence in Indonesia Manufacturing Companies - Widiatmoko, Jacobus; Indarti, MG. Kentris (Jurnal Dinamika Akuntansi, 2019)
Current earnings can be used by investors to predict future earnings if the earnings are of high quality (persistent). This study examines the effect of book tax differences, operating cash flow and debt level on earnings persistence. This study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2016 as populations. Based on data analysis with ordinary least square regression, the results show that two hypotheses are accepted, namely temporary book tax differences and cash flow from operating. As hypothesized, book tax differences negatively affect earnings persistence and operating cash flow has a positive effect on earnings persistence. Meanwhile, permanent book tax differences have not been proven to influence earnings persistence.